Cash Crop Choice and Income Dynamics in Rural Areas: Evidence for Post-Crisis Indonesia - Stephan Klasen; Jan Priebe; Robert Rudolf (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2010)
In this paper we investigate the factors affecting income levels, income growth, and poverty reduction in rural Indonesia following the crisis of 1997/98. We particu- larly investigate the relative roles of non-farm incomes, productivity improvements achieved via changes in crops versus improvements on the same crops, and demographic changes induced by the crisis on income dynamics in rural Indonesia. Using a unique household panel data set for Central Sulawesi that allows us to control for a large set of household and geographical characteristics, household fixed effects as well as endogeneity issues, we find that falling household size and the adoption and intensification of new cash crop varieties can explain a substantial part of the observed post-crisis developments. Moreover, we compare our results to cross-sectional data from SUSENAS, Indonesiaś large scale national household survey. While the overall determinants of rural incomes are very similar across both data sets, we find that the importance of agricultural self-employed income seems to be higher in Central Sulawesi than in most other parts of Indonesia. Although several factors could explain these differences, lessons from our Central Sulawesi data suggests that unexploited potentials in the production of cash crops in other areas of Indonesia might contribute to these findings.
Keywords: I31; Q12; Q15; R13; 330; Crop choice; Income diversification; non-farm sector; rural development; Indonesia